Development of high-speed installation design and wire galvanizing technology - D. B. Zuev (Литьë и металлургия)
The article presents a new design of a high‑speed small‑size wire galvanizing plant. Electrolytic method of zinc deposition is implemented using two methods of current supply. The quality of the zinc coating was evaluated. Practical recommendations have been developed for the method of applying zinc coating. The new galvanizing unit reduces dimensions compared to existing wire galvanizing units and increases wire pulling speed.